IDENTIFIKASI PENGETAHUAN IBU TENTANG PELAKSANAAN PIJAT BAYI DALAM POLA TIDUR BAYI USIA 0-12 BULAN DI WILAYAH KERJA PUSKESMAS BOTUPINGGE - Nurul Maghfirah Mohamad; Dewi Modjo; Rini Asnawati; Indrawati (LPPM STIKES BINA GENERASI POLEWALI MANDAR, 2026)
One of the factors influencing infant growth and development is sleep and rest patterns, which impact the quantity and quality of sleep. The importance of maternal knowledge regarding infant massage is directly related to managing poor infant sleep patterns. Therefore, good knowledge will impact the infant's sleep needs being met. The purpose of this study was to identify maternal knowledge regarding infant massage implementation in infants aged 0-12 months in the Botupingge Community Health Center (Puskesmas) work area. The research design used descriptive quantitative research. The sampling technique used was total sampling, with 45 respondents. The results showed that the majority of parents (18 parents) had poor knowledge regarding infant massage implementation, and the majority (32 parents) had poor infant sleep patterns. The conclusion is that parents' knowledge regarding infant massage implementation is lacking, resulting in the average infant having poor sleep patterns. This study recommends the need for educational efforts to improve maternal knowledge regarding infant massage implementation. Keywords: Maternal Knowledge, Infant Massage, Sleep Patterns